The patient at the centre: evidence from 17 European integrated care programmes for persons with complex needs - Thomas Czypionka; Markus Kraus; Miriam Reiss; Erik Baltaxe; Josep Roca; Sabine Ruths; Jonathan Stokes; Verena Struckmann; Romana Tandara Haček; Antal Zemplényi; Maaike Hoedemakers; Maureen Rutten-van Mölken (BMC, 2020)
Abstract Background As the prevalence of multi-morbidity increases in ageing societies, health and social care systems face the challenge of providing adequate care to persons with complex needs. Approaches that integrate care across sectors and disciplines have been increasingly developed and implemented in European countries in order to tackle this challenge. The aim of the article is to identify success factors and crucial elements in the process of integrated care delivery for persons with complex needs as seen from the practical perspective of the involved stakeholders (patients, professionals, informal caregivers, managers, initiators, payers). Methods Seventeen integrated care programmes for persons with complex needs in 8 European countries were investigated using a qualitative approach, namely thick description, based on semi-structured interviews and document analysis. In total, 233 face-to-face interviews were conducted with stakeholders of the programmes between March and September 2016. Meta-analysis of the individual thick description reports was performed with a focus on the process of care delivery. Results Four categories that emerged from the overarching analysis are discussed in the article: (1) a holistic view of the patient, considering both mental health and the social situation in addition to physical health, (2) continuity of care in the form of single contact points, alignment of services and good relationships between patients and professionals, (3) relationships between professionals built on trust and facilitated by continuous communication, and (4) patient involvement in goal-setting and decision-making, allowing patients to adapt to reorganised service delivery. Conclusions We were able to identify several key aspects for a well-functioning integrated care process for complex patients and how these are put into actual practice. The article sets itself apart from the existing literature by specifically focussing on the growing share of the population with complex care needs and by providing an analysis of actual processes and interpersonal relationships that shape integrated care in practice, incorporating evidence from a variety of programmes in several countries.